Применение суперкомпьютеров СКИТ для разработки и выполнения параллельных геофизических программ - Тульчинский, В.Г.; Тульчинский, П.Г. (Кибернетика и системный анализ, 2009)
Описано досвід розробки паралельних програм для сейсморозвідки. Сейсмічні дані зазвичай дуже великі і їх легко декомпозувати. Ці властивості призводять до аналогічних технологій розпаралелювання для таких різних завдань, як потрасна обробка, міграції й кінцево-різницеве моделювання. Розробка проекту розпаралелювання описана в термінах мови шаблонів паралельного програмування й методу аналізу ієрархій Т. Сааті. Досліджено питання ефективності паралельної обробки даних. The development of parallel programs for seismic exploration is described. Seismic datasets are usually extensive and have easily decomposable structure. These features result in similar paralleling techniques for different problems such as trace-by-trace processing, migrations and finite-difference modeling. The paralleling project development is described in terms of Pattern Language for Parallel Programming and Analytic Hierarchy Process. The parallel data processing is analyzed for efficiency.